Hexagonal NiS nanobelts as advanced cathode materials for rechargeable Al-ion batteries. Issue 68 (4th August 2016) - Yu, Zhijing; Kang, Zepeng; Hu, Zongqian; Lu, Jianhong; Zhou, Zhigang; Jiao, Shuqiang
Abstract : NiS nanobelts served as cathode materials for Al-ion batteries based on an AlCl3 /[EMIm]Cl ionic liquid electrolyte. Abstract : Hexagonal NiS nanobelts served as novel cathode materials for rechargeable Al-ion batteries based on an AlCl3 /[EMIm]Cl ionic liquid electrolyte system. The nano-banded structure of the materials can facilitate the electrolyte immersion and enhance Al 3+ diffusion. The hexagonal NiS nanobelt based cathodes exhibit high storage capacity, good cyclability and low overpotential.